2022
DOI: 10.1063/5.0125879
|View full text |Cite
|
Sign up to set email alerts
|

Structure of diopside, enstatite, and magnesium aluminosilicate glasses: A joint approach using neutron and x-ray diffraction and solid-state NMR

Abstract: Neutron diffraction with magnesium isotope substitution, high energy x-ray diffraction, and 29Si, 27Al, and 25Mg solid-state nuclear magnetic resonance (NMR) spectroscopy were used to measure the structure of glassy diopside (CaMgSi2O6), enstatite (MgSiO3), and four (MgO) x(Al2O3) y(SiO2)1−x−y glasses, with x = 0.375 or 0.25 along the 50 mol. % silica tie-line (1 − x − y = 0.5) or with x = 0.3 or 0.2 along the 60 mol. % silica tie-line (1 − x − y = 0.6). The bound coherent neutron scattering length of the isot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(21 citation statements)
references
References 72 publications
1
20
0
Order By: Relevance
“…The Huang potentials utilized in this work report an average of 5% less Al [5] in comparison. However, these percentages agree with NMR work conducted by Gammond F I G U R E 1 3 Fraction of Al [5] with 50-55 mol% SiO 2 from this work compared with nuclear magnetic resonance (NMR) results from Lamberson, 44 Mohammadi et al, 43 Neuville et al, 45 Guignard and Cormier, 39 and with ReaxFF from Yeon et al 40 et al in compositions with 60 mol% SiO 2 at the same [Al 2 O 3 ]/[MgO] ratios (Table 2). At the equivalence point (R = 1), reported literature results show 10-21% Al [5] for 50-60 mol% SiO 2 which agrees with the Pedone and Wang potentials.…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…The Huang potentials utilized in this work report an average of 5% less Al [5] in comparison. However, these percentages agree with NMR work conducted by Gammond F I G U R E 1 3 Fraction of Al [5] with 50-55 mol% SiO 2 from this work compared with nuclear magnetic resonance (NMR) results from Lamberson, 44 Mohammadi et al, 43 Neuville et al, 45 Guignard and Cormier, 39 and with ReaxFF from Yeon et al 40 et al in compositions with 60 mol% SiO 2 at the same [Al 2 O 3 ]/[MgO] ratios (Table 2). At the equivalence point (R = 1), reported literature results show 10-21% Al [5] for 50-60 mol% SiO 2 which agrees with the Pedone and Wang potentials.…”
Section: Discussionsupporting
confidence: 88%
“…Instead, Mg coordination changes depending on the molar percentage of SiO 2 in the composition. This is a possible explanation for the observations made by Mohammadi et al 43 in which it was concluded that there was little evidence of four-coordinated Mg acting as a network former. From their work using 25 Mg NMR, the absence of spectroscopic differences between Ca-containing aluminosilicates and Mg compositions suggested that Mg behaves similarly to Ca (calcium ions are understood to behave primarily as network modifiers).…”
Section: Ta B L Ementioning
confidence: 81%
See 3 more Smart Citations